Health psychology - French, David (David P.); British Psychological Society (Chichester, West Sussex : Wiley-Blackwell ; [Leicester] : British Psychological Society, 2010)
'The second edition of Health Psychology is substantially revised and updated to reflect key developments and the latest research in this rapidly expanding discipline. With 31 chapters written by leading international health psychologists, the text provides a high quality and up-to-date overview of current Health Psychology science and practice, presented in an organised and engaging format. The chapters of this new edition are explicitly structured around the Stage 1 curriculum of the British Psychological Society's Division of Health Psychology, offering the equivalent level to a Health Psychology masters degree. The text provides students with a critical, thought-provoking introduction to the subject, clearly and critically outlining the major areas of theory and research. Each chapter is authored by a leading expert in the subject and can stand alone as a complete overview of a particular area. Taken together, the chapters provide a cohesive and integrated look at this important field'--Provided by publisher
Includes bibliographical references and index
Keywords: Psychology, Clinical